Endangering Sacred Groves of a Non forested Region in Kerala, India and Strategies for their Conservation - Warrier, Kannan C. S.; Kunhikannan, C.; Sasidharan, K. R. (Indian Forester, 2015)
Alappuzha is the only district in Kerala state without natural forests. Therefore, sacred groves of this region attract utmost attention as they are the only remnants of natural forests once present. An exhaustive survey carried out in Alappuzha district revealed the presence of 1128 sacred groves varying in extent. Plant species numbering 687 were recorded from the sacred groves covering an area of 83.55 ha of Alappuzha district. They belonged to 493 genera and 127 families. Many valuable medicinal plants and wild relatives of cultivated species have been recorded which are important in species improvement programmes. Twenty-seven species were found to be endemic to Western Ghats. Most of the sacred groves in Alappuzha were proved to be invaluable resource pockets of floristic diversity. Many sacred groves in the district face threat due to the dense human population and change in socio-economic status. Break up of ancestral joint family system to nuclear families is the major reason for deterioration of these valuable resources. ’Ulladans’, the tribal community collect canes and firewood indiscriminately. Overexploitation of the resources by them has lead to its retrogression to a great extent. Removal of litter alongwith the seeds from the floor has also resulted in retrogression by hindering the natural regeneration process. Exotic weeds namely, Mikania micrantha, Lantana camera and Chromolaena odorata overgrow the native species and play a major role in degradation. A detailed database on important sacred groves containing all the vital information including soil type, nutritional status, flora, fauna, plant associations, population structure, cultural and religious aspects and management operations will help in prescribing site specific conservation strategy.